PELATIHAN READING SKILL DALAM PENULISAN ARTIKEL ILMIAH BERSAMA PERSEKUTUAN PELAJAR RIRING-RUMASOAL AMBON - Fadli, Zul; Ramdhan, Rizki Muhammad; Sakir, Ahmad Rosandi (Universitas Pattimura, 2022)
Reading Skill as a basic reading ability for students and a tool for students to find out the meaning in writing scientific articles. The faster the student's reading ability, the greater the opportunity to understand what is read. Community Service through training in reading skills to the Riring-Rumasalah Ambonese Student Association (PRRA) which is a combination of students from Riring Village and Rumassalah Village, West Seram Regency, Maluku Province to add insight, improve thinking skills, create imagination space, increase level literacy, and improve the ability to write scientific articles. Service activities are carried out with a mentoring approach per group and are going well. need more intense and periodic education to improve the reading ability of PRRA students which is very much needed in writing scientific articles